(untitled) (American Journal of Islam and Society, 2002)
This paper explores the role of an epistemic community’s influence upon American foreign policy vis-a-vis political ]slam. lt tries to account for American hostility toward Islamic resurgence by employing the constructivist paradigm. ln this regard, the following observations are highlighted: The epistemic community in question has two rival wings: Accommodationist and Confrontationalist, the resulting foreign policy view is a func tion of the dialectic between them; and constructivism coupled with the concept of epistemic communities helps explain the dynamics associated with the role of connoisseur recommendation in formulating American foreign policy toward political lslam.